2019
DOI: 10.1098/rsif.2019.0355
|View full text |Cite
|
Sign up to set email alerts
|

The impact of balloon-expandable transcatheter aortic valve replacement on concomitant mitral regurgitation: a comprehensive computational analysis

Abstract: The aortic and mitral valves function in a reciprocal interdependent fashion. However, the impact of transcatheter aortic valve replacement (TAVR) on the aortic–mitral continuity and severity of mitral regurgitation (MR) are poorly understood. In this study, a comprehensive engineering analysis was performed to investigate the impact of TAVR on MR severity and left heart dynamics in a retrospective patient case who harbours bicuspid aortic valve stenosis and concomitant functional MR. The TAVR procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…In particular, the effect of neochordae length on postrepair MV dynamics was investigated. However, for physiologically accurate simulations and rigorous evaluation of MV repair treatments, the intraventricular blood dynamics and the structural mechanics of the valves should be modeled together, an area where fluid‐structure interaction (FSI) modeling is required …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the effect of neochordae length on postrepair MV dynamics was investigated. However, for physiologically accurate simulations and rigorous evaluation of MV repair treatments, the intraventricular blood dynamics and the structural mechanics of the valves should be modeled together, an area where fluid‐structure interaction (FSI) modeling is required …”
Section: Introductionmentioning
confidence: 99%
“…However, for physiologically accurate simulations and rigorous evaluation of MV repair treatments, the intraventricular blood dynamics and the structural mechanics of the valves should be modeled together, an area where fluid-structure interaction (FSI) modeling is required. [15][16][17][18] In the present work, we employed a previously developed left heart (LH) FSI model with multiple levels of PML prolapse 19 to simulate transapical neochordae implantation and better understand the biomechanical interaction between the neochordae and the LH structures. Specifically, we assessed the magnitude and time course of the force exchange between the native mitral apparatus, the transapical sutures, and the blood flow under baseline, prerepair, and postrepair states throughout the cardiac cycle.…”
mentioning
confidence: 99%
“…However, several researchers, including our group, have shown that it is a promising method in the field of cardiovascular biomechanics. It has been used to study the mitral valve mechanics (47), left ventricular flow (29), TAVR impact on MR (8), and wall shear stress of abdominal aortic aneurysm (1). Because of the limitations of the Abaqus SPH formulation, the small-scale flow features close to the wall boundary may not be accurately resolved.…”
Section: Evaluation Of the Vt Methodsmentioning
confidence: 99%
“…Subsequently, it was used to assess several diseased mitral valve states [ 43 , 44 , 45 , 46 ] and applications of medical devices designed to correct them [ 47 , 48 , 49 , 50 ]. Besides the mitral valve, other valves have been studied using the same methods [ 42 , 51 , 52 , 53 , 54 , 55 ]. The SPH method has been validated to study the hemodynamics of the left ventricle [ 29 ].…”
Section: Applicationsmentioning
confidence: 99%